Impact of Arbuscular Mycorrhizal Symbiosis on Photosynthetic, Antioxidant Enzyme, and Water Flux Parameters in Salt-Stressed Chickpea (Cicer arietinum) Plants - Pooja Pooja; Sarita Devi; Sridevi Tallapragada; Yogesh K. Ahlawat; Nisha Sharma; Pankaj Kasnia; Nita Lakra; Rosa Porcel; Jose M. Mulet; Khalid M. Elhindi (Agronomy)
Globally, escalating soil salinization poses significant abiotic stress, disproportionately impacting crops like chickpea (Cicer arientinum L.). This legume exhibits high sensitivity to salinity, which disrupts various physiological and metabolic processes, ultimately hindering growth and productivity. AMF (arbuscular mycorrhizal fungus) reduces salt’s detrimental effects on plants’ growth by bolstering the plant’s antioxidant defense system, effectively reducing the damage caused by oxidative stress. In this study, the impact of AMF on salinity stress alleviation in chickpea was investigated in pot-grown experiments. Rhizophagus fasciculatus was used to inoculate the seeds of three different chickpea varieties (HC-3, CSG-8962, and C-235), and the physiological and biochemical changes of the AMF-inoculated and non-inoculated chickpea plants were studied. When exposed to salinity stress, the plants exhibited decreased leaf relative water content (RWC %) (21.13–31.30%), increased leaf relative stress injury, decreased chlorophyll content (45.22–58.24%), photochemical quantum yield, photosynthetic rate, transpiration rate, and stomatal conductance as compared to the control plants, but opposite results were observed in AMF colonized plants. A 9.16% to 14.79% increase in chlorophyll content was reported after AMF colonization. The activities of antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and peroxidase (POX) were increased by salt stress. They were further enhanced by AMF inoculation SOD activity by 20.3% to 23.3%, CAT activity by 65.7% to 78.7%, and POX activity by 32.7% to 39.3%. The findings clearly show that AMF Rhizophagus fasciculatus, via enhancing RWC, photosynthetic parameters, and antioxidant enzymes, can mitigate salinity stress in chickpeas.